Potential, economic advantages and constraints of agroforestry in the fight against global warming: the case of Djilor District (Fatick, Senegal) - Daniel, Gomis; Agnès Daba, Thiaw-Benga; Sidia Diaouma, Badiane; Babacar, Faye; Aliou, Guisse; Aminata, Ndiaye (Revue Ecosystèmes et Paysages, 2024)
Global warming threatens the well-being of millions of people around the world. Faced with this situation, there has been renewed interest in understanding the role of ecosystem goods and services in mitigating this phenomenon. With this in mind, the aim of the present study was to assess the role of agroforestry in reducing CO2 emissions and the economic advantage it offers populations in terms of carbon credits, while analyzing the local constraints linked to its practice. To achieve this, surveys were carried out in 513 households. Carbon stored in woody biomass was assessed using "allometric models", based on inventory data collected randomly on 72 plots of 1600 m2. The number of plots was defined on the basis of a pre-inventory. The results revealed a species richness of 22 species characterized by an average diversity due to a Shannon index of 3.95 bits. Biological and phytogeographical species types show the dominance of mesophanerophytes and Sudanian and Sudano-Zambezian chorologies. The average stock of atmospheric carbon sequestered in this stand (7.5 tC.ha-1), demonstrates the compensatory role of ligneous plants for anthropogenic CO2 emissions. Assessment of the economic value of this potential, which amounts to 49,590.6 f CFA/tCO2/ha, reveals the existence of an opportunity that farmers could exploit within the framework of carbon credits. There are, however, local constraints to the development of agroforestry in the area, chiefly the perception of the duality between trees and agricultural production, grazing practices, rainfall deficits and the lack of production factors. This work shows the effectiveness of agroforestry in the fight against global warming and the vulnerability of populations, with a view to improving the practice for the benefit of the planet and communities.